PREDICTING LAND USE CHANGES USING MARKOV CHAIN ANALYSIS AND HIERARCHICAL ANALYSIS OF PUBLIC SERVICE CENTERS IN BANDA ACEH CITY - Rahmaniar, Meutia Hanum; Rusdiana, Siti; Zahnur, Zahnur (PATTIMURA UNIVERSITY, 2024)
The city of Banda Aceh, as the center of development in its region, is faced with a series of complex problems, one of which is the lack of optimal distribution of public service centers throughout the city. Banda Aceh City Central Statistics Agency (BPS) documents 2012-2022 and Banda Aceh City Spatial Plan (RTRW) documents 2009-2029 related to this research. Data in tabulated and descriptive form includes geographical conditions of the research area, land use area, types of facilities and their numbers, population, and distance between areas, and maps related to the research. This study aims to see land use conditions using the markov chain method and provide an overview of the public service center system of Banda Aceh City using the Scalogram method, centrality index, and gravity. Based on Markov chain analysis, land use predictions indicate that residential areas, offices and trade, tourism, worship, and sports facilities will continue to increase, while water bodies, green open spaces (RTH), and non-green open spaces (RTNH) will continue to decline. Predictions until 2039 show that conditions have begun to stabilize. Scalogram analysis takes into account hierarchy based on the type of facilities available, centrality index that calculates hierarchy based on many available facilities, and gravitational interaction that takes into account the strength of interaction between sub-districts shows that Kuta Alam District has the potential to become a major service center in Banda Aceh City. This sub-district has the most complete facilities, supported by the highest interaction value.